Strengthening Students’ Learning Enthusiasm Through Love and Appreciation: A Case Study at SMK Negeri 3 Buduran Sidoarjo - Riskha Sinta Syah Devi; Rianda Usmi; Oksiana Jatiningsih; Siti Maizul Habibah (Jurnal Pendidikan Terapan, 2026)
Purpose: Analyzing the strengthening of enthusiasm for learning through providing the need for love and appreciation in overcoming the phenomenon of students not advancing to class at SMK Negeri 3 Buduran Sidoarjo during the implementation of the Independent Curriculum. Methods: This research uses a qualitative approach with a case study type. Research subjects included school principals, teachers and students who experienced not being promoted to grade. Data collection techniques are carried out through observation, interviews and documentation. Data analysis uses data reduction, data presentation, and drawing conclusions. Findings: The research results show that the phenomenon of not being promoted to grade is influenced by internal and external factors, such as low learning motivation, lack of family support, learning strategies that do not meet students' needs, and students' psychological needs that have not been met. Strengthening the enthusiasm for learning through fulfilling the needs for love and appreciation increase learning participation, self-confidence, discipline and motivation of students. Research Implications: This research has the implication that fulfilling the need for love and appreciation can be a pedagogical strategy in preventing the phenomenon of not being promoted. These findings can also be a reference for schools and teachers in designing learning that is more humane, supportive and centered on students' needs in implementing the Independent Curriculum. Originality: The novelty of this research lies in the focus on strengthening enthusiasm for learning through the perspective of the need for love and appreciation as a strategy to overcome the phenomenon of not being promoted to grade, especially in the context of implementing the Independent Curriculum in vocational high schools.